Factors Affecting the Risk and Financial Performance of Banks in Indonesia - Sudrajat, Anastasya Yulianti; Ramadania, Zafira; Leon, Farah Margaretha (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This study aims to determine the effect of systematic risk (Beta) and COVID-19 as independent variables, then non-performing loans (NPL), liquidity risk (LR), solvency risk (SR), bank risk (Z-score), and ownership type (OT) as control variables on the dependent variables financial performance proxied using ROA and ROE. The research method is quantitative covering data from 17 banks listed in Indonesia over a six-year period (2017-2022) and using panel data regression analysis technique processing. The addition of new independent variables in this study is operational risk which has a positive and significant effect on ROA and ROE. In addition, liquidity risk and solvency risk also have a positive and significant effect on ROA and ROE, while ownership type variables have negative and significant effect on ROA and ROE. Understanding the impact of these factors will help companies make the right decisions to reduce risk and optimize their financial performance in Indonesia. The implication for financial managers is to maximize the long-term debt and leverage of the company which aims to support the company’s operational activities. This research also provides important information for investor in making investment by assessing companies that have good financial performance.